Asian American Spring Festival 1987 Flyer 08 (SJSU Asian American Studies Department, 2024)
Flyer for the Asian Spring Festival Cultural Day, held on Wednesday, April 1 at 11:00 AM – 2:00 PM in the Amphitheater/Upper Pad.